Examining The Policy Narrative and The Role of the Media in the Policy Response to the Covid-19 Crisis in Indonesia - Muryanto, Febriana; Sukristyanto, Agus; Juliswara, Vibriza (International Journal of Science, Technology & Management, 2022)
This paper aims to investigate the relationship narratives presented in the media and their role in influencing the policymaking process regarding the COVID-19 response in Indonesia. The study is based on an analysis of online news content and in-depth interviews with political advisers to the president and ministers as well as public health experts who were invited to the core group of policymakers. Analysis of the narrative policy framework reveals the relationship between the government's response and the changing tone of media coverage. The study also finds that the media have become an influential platform influencing policy agenda setting.